Javanese Muslims in the metropolitan Bangkok: fiqh at-ta'ayusy perspective - Yusdani,; Januariansyah Arfaizar,; Srawut Aree, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The article describes the success of the minority life of the Javanese-Indonesian Muslim community in Sathorn Bangkok, Thailand. The main problem that is the focus of the discussion in this paper is how are the dynamics, challenges, struggles, and lives of the Javanese Muslim community in the fields of religion, politics, culture, and economy still survive today. This study of the life of the Muslim community of Javanese descent is using qualitative field research methods with the interview, observation, and documentation data collection techniques. The framework and approach used in this paper are to integrate and combine the sociology of knowledge, Islam, and Javanese culture. While the analysis used in this study is fiqh at-ta'ayusy (coexistence) an analytical method using the perspective of respecting equality, mutual respect, living in peace, and living side by side as fellow Thai citizens. This coexistence and equality cover the fields of religious life, education, culture, economy, politics, and culture. The results of the study in this paper indicate that the success of the Javanese Muslim minority diaspora community in religious, political, cultural, and economic aspects in Kampung Jawa in Bangkok Thailand is due to their ability to adapt, live peacefully, in harmony with the Thai community, especially in Sathorn. The success of the struggle and the life of the Muslim community is inspired by Islamic values such as inclusiveness, and respect for others, and Javanese cultural values as their heritage values, such as being polite, tolerant, and adaptive.